The Tradition of Maiyah Juguran Syafaat as New Tradition of Modern Islamic Da'wah - Suprapto, Yuni; ., Wasino; Arsal, Thriwaty; Priyanto, At. Sugeng; Wilonoyudho, Saratri; Munir AP, Muh Misbahul (Journal of Ecohumanism, 2025)
This article is the result of research conducted at the Jamaah (members/followers/congregation) Maiyah Juguran Syafaat for the study purpose to find out some of the traditions of modern pengajian (recitation gathering) of the Jamaah Maiyah Juguran Syafaat, qualitative research methods were used in this study by interviewing the jamaah and Maiyah Juguran Syafaat activists, participatory observation and implementation documentation Maiyah Juguran Syafaat modern pengajian activities. The sampling technique uses snowball sampling, and the data analysis tool uses source triangulation and technical triangulation. The research results are as follows, modern pengajian traditions of Juguran Syafaat include: 1) Scientific Dialectic Tradition; 2) Integration Traditions of various cultures and groups; 3) Tawassullan (intensive prayer) Tradition; 4) Tradition of determining the theme of joint learning activities; 5) The tradition of accepting all diversity of the congregation; 6) Traditions of approaches to various scientific disciplines; 7) Tradition of self-transformation; and 8) Tadabbur (contemplation) Tradition. The conclusion of this study is the tradition of modern pengajian of Maiyah Juguran Syafaat which consists of eight traditions combining traditional Islamic traditions that have initially existed and new traditions in accordance with the era progression.